Clinical hypnosis can reduce lower urinary tract symptoms in individuals with chronic pain. Issue 1 (15th November 2022) - McKernan, Lindsey C.; Connors, Erin L.; Ryden, Anna M.; Finn, Michael T. M.; Kim, Ahra; Vandekar, Simon N.; Dmochowski, Roger R.; Reynolds, W. Stuart
Abstract: Study Purpose: Lower urinary tract symptoms (LUTS) can occur in chronic pain populations at high rates and drastically affect quality of life. Hypnosis is a nonpharmacological treatment used in chronic pain known to have beneficial implications to health outside of pain reduction. This study evaluated the potential for hypnosis to reduce LUTS in a sample of individuals with chronic pain, if baseline LUTS severity affected outcomes, and specific LUTS that may respond to hypnosis. Methods: Sixty‐four adults with chronic pain and LUTS at a level of detectable symptom change (American Urological Association Symptom Index, AUASI ≥ x02265 3) participated in an 8‐week group hypnosis protocol. Participants completed validated assessments of LUTS, pain, and overall functioning before, after, 3‐ and 6‐months posttreatment. Linear mixed effects models assessed improvement in LUTS over time while accounting for known factors associated with outcome (e.g., age, gender). The interaction of baseline symptom severity and treatment assessed the potential effect of baseline symptoms on change scores. Results: Participants experienced significant and meaningful improvements in LUTS following group hypnosis ( p = 0.006). There was a significant interaction between baseline symptom severity and treatment ( p < 0.001), such that those with severe symptoms experienced the most pronounced gains over time (e.g., an 8.8 point reduction). Gains increased over time for those with moderate and severe symptoms. Changes in LUT symptoms occurred independently of pain relief. Conclusions: This pilot study suggests hypnosis has the potential to drastically improve LUTS in individuals with chronic pain, even when pain reduction does not occur. Results provide initial evidence for the treatment potential of hypnosis in urologic pain (and possibly non‐pain/benign) populations, with randomized trials needed for definitive outcomes.